Optimization of xylose production from rice straw using response surface methodology (RSM) - Nur'atiqah, Norhalim (2010)
The rice straw is an abundant biomass produced every year in Malaysia and also well known as agricultural residues in renewable resource. The biomass residues often burned at open field and caused in environmental problem. The rice straw contains about 25% hemicelluloses, the next most abundant polysaccharides in nature. The hemicelluloses will degrade into its reducing sugar which is xylose in enzymatic hydrolysis process by using xylanase. This research is study on optimization of xylose production from rice straw by using Response Surface Methodology (RSM) based on Central Composite Design (CCD). The parameters used to obtain xylose production were temperature, agitation rate and xylanase concentration during enzymatic hydrolysis. The rice straw was treated by alkaline hydrolysis and acid hydrolysis continuously. Then, the conventional method was used to determine the best ranges of parameters. The best ranges were used in RSM for optimization process. The optimum production of xylose was achieved at temperature of 55⁰C, agitation rate of 155 rpm and 2.06 mg/ml of xylanase concentration. The xylose production obtained was 0.2716 mg/ml after optimization process. Before optimization, the xylose concentration was 0.2051 mg/ml. As a conclusion, the production of xylose has been successfully optimized from rice straw using RSM with increment of 32.43%.